A Roadmap to Inform the Implementation of Evidence-Based Collaborative Care Interventions in Communities: Insights From the Michigan Mental Health Integration Partnership - Rusch, Amy; DeCamp, Lindsay M.; Liebrecht, Celeste M.; Choi, Seo Youn; Dalack, Gregory W.; Kilbourne, Amy M.; Smith, Shawna N. (Frontiers in Public Health, 2021)
Background: In spite of increasing calls for further spread of evidence-based collaborative care interventions (EBIs) in community-based settings, practitioner-driven efforts are often stymied by a lack of experience in addressing barriers to community-based implementation, especially for those not familiar with implementation science. The Michigan Mental Health Integration Partnership (MIP) is a statewide initiative that funds projects that support implementation and uptake of EBIs in community-based settings. MIP also provides an in situ implementation laboratory for understanding barriers to the uptake of EBIs across a variety of settings. We report findings from a Statewide qualitative study of practitioners involved in MIP projects to garner their perspectives of best practices in the implementation of EBIs. Methods: Twenty-eight semi-structured interviews of practitioners and researchers from six MIP Projects were conducted with individuals implementing various MIP EBI projects across Michigan, including stakeholders from project teams, implementation sites, and the State of Michigan, to identify common barriers, challenges, and implementation strategies deployed by the project teams, with the purpose of informing a set of implementation steps and milestones. Results: Stakeholders identified a number of barriers to and strategies for success, including the need for tailoring program deployment and implementation to specific site needs, development of web-based tools for facilitating program implementation, and the importance of upper level administration buy-in. Findings informed our resultant community-based Implementation Roadmap, which identifies critical steps across three implementation phases--pre-implementation, implementation, and sustainability—for implementation practitioners to use in their EBI implementation efforts. Conclusion: Implementation practitioners interested in community-based EBI implementation often lack access to operationalized implementation “steps” or “best practices” that can facilitate successful uptake and evaluation. Our community-informed MIP Implementation Roadmap, offering generalized steps for reaching successful implementation, uses experiences from a diverse set of MIP teams to guide practitioners through the practices necessary for scaling up EBIs in community-based settings over pre-implementation, implementation and sustainability phases.